GEMA ANTING (Community Movement of Anticipating Stunting) By Introduction Tofu Nuggets in Desa Sukaraja Kabupaten Ciamis - Dini Ariani; Sandriani Sandriani; Hani Septiani (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Stunting is a sign that children are not developing well physically or psychologically, especially in the first 1000 days of life. Desa Sukaraja is an experimental village formed by Puskesmas and local government as an effort to reduce the stunting incidence, with a stunting focus location program (Lokus) in early 2020. This program is also supported by the results of abundant natural resources, especially in producing processed soybeans, namely tofu. The aim of this community service activity is to increase the knowledge of pregnant women and mothers of toddlers about processing tofu basic ingredients into tofu nugget as an effort to anticipate stunting. The method used is by providing health education about stunting and demonstrating the making process of tofu nuggets. The target of this activity is all 28 pregnant women and mothers of children under five who come to Posyandu Brunggendis 1. The result of this program reveals an increase in knowledge about stunting and processing tofu into tofu nuggets. Pregnant women and mothers of toddlers know and understand the incidence of stunting, and know how to make tofu nuggets.